Prevention, surveillance, and scorpion accident control: an integrative review (Research, Society and Development, 2022)
There are several species of scorpions. Among these, three, Tityus serrulatus, Tityus bahiensis, and Tityus stigmurus are found in Brazil and present medical and veterinary importance, implying enormous challenges to the public health regarding population and environmental health. The scorpions are the main responsible for accidents among venomous animals in Brazil, being T. serrulatus the most dangerous species, given its wide distribution in the country, in urban centers, and the vast toxic potential of its venom. Methodology: based on this information, given the theme’s importance to public health, and bibliographical scarcity, a systematic integrative review was elaborated in databases: BVS; REDALYC, and CAPES. Objective: better highlight the information in the context of prevention, surveillance, and control of scorpions in urban areas through a scientific compilation produced in the last ten years. Results: six integrative content categories were systematized on the topic. Closing remarks: scorpions had their environment devastated by anthropomorphism and adapted to the imposed urban conditions. Correct compliance with hygienic-sanitary measures and active population surveillance favors the reduction of scorpionism. Complementary, the mechanical capture corresponds to the most effective form of scorpion control. Nonetheless, chemical, and biological controls, focusing on the Tityus genus, especially, T. serrulatus, need further studies to prove their real effectiveness.